2007
DOI: 10.1021/jp066464m
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ethyl Peroxy Radical Conformers via Cavity Ringdown Spectroscopy of the Ã-X̃ Electronic Transition

Abstract: Both stable conformers, trans (T) and gauche (G), of the ethyl peroxy radical and its perdeutero analogue have been observed via cavity ringdown spectroscopy (CRDS) of the A2A'-X2A' ' electronic transition in the near-IR. Assignments of specific spectral lines to the electronic transition origin (T00), to observed vibrational hot bands, and to the COO bend and the O-O stretch vibrations are given with the help of equation of motion (EOMIP) quantum chemical calculations. In particular, spectral information for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 27 publications
6
50
0
Order By: Relevance
“…Our recent CRDS studies of C 2 H 5 O 2 and C 2 D 5 O 2 , under room-temperature conditions 17 identified the G and the T conformers of the radicals. However, due to the rotational congestion of these spectra, no accurate values of the rotational constants nor the spin-rotation constants were reported.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our recent CRDS studies of C 2 H 5 O 2 and C 2 D 5 O 2 , under room-temperature conditions 17 identified the G and the T conformers of the radicals. However, due to the rotational congestion of these spectra, no accurate values of the rotational constants nor the spin-rotation constants were reported.…”
Section: Introductionmentioning
confidence: 95%
“…As noted previously its conformers can be labeled as G ͑CCOO dihedral angle Ϯ60°͒, which has a C 1 symmetry, and T ͑CCOO dihedral angle of Ϯ180°͒, which has C s symmetry. In 2007, Rupper et al 17 observed and analyzed the room temperature CRDS spectra of both conformers of this radical. Based upon high level quantum chemistry calculations, they determined that the G conformer was about 80 cm −1 lower in energy than the T conformer in the X state.…”
Section: A the G Conformer Of The Ethyl Peroxy Radicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent CRDS experiments 13,[15][16][17][18][19][20][21][22] on various alkyl peroxy radicals have demonstrated the sharp, structured à -X spectra that can be used to distinguish among different R groups, and even among different isomers and conformers of the same RO 2 radical. However, they have been only able to resolve rotational contours because of the congestion caused by the overlap of different rotational lines of the same, and also different conformers at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…(89) Radical spectroscopy has also been the subject of ringdown studies, as demonstrated by early investigations of OH in flames (86,123,126,127) and the SH radical in an absorption cell. With the high sensitivity of ringdown spectroscopy, abundant rotational and vibrational data have been obtained for methyl peroxy (CH 3 O 2 ), (128) trifluoromethyl peroxy (CF 3 O 2 ), (129) (130) propyl peroxy (C 3 H 7 O 2 ), (131) phenyl peroxy (C 6 H 5 O 2 ), (132) and ethyl peroxy (C 2 H 5 O 2 ) (133) radicals, whose spectra in UV or visible (VIS) are typically overlapped so that little spectroscopic information can be obtained. An early demonstration of the extreme sensitivity of (80) In so doing, they demonstrated per pass absorbance detection limits on the order of 10 −7 .…”
Section: Fundamental Molecular Spectroscopymentioning
confidence: 99%